2016
DOI: 10.1002/2016ja022841
|View full text |Cite
|
Sign up to set email alerts
|

Van Allen Probes observations of electromagnetic ion cyclotron waves triggered by enhanced solar wind dynamic pressure

Abstract: Magnetospheric compression due to impact of enhanced solar wind dynamic pressure Pdyn has long been considered as one of the generation mechanisms of electromagnetic ion cyclotron (EMIC) waves. With the Van Allen Probe‐A observations, we identify three EMIC wave events that are triggered by Pdyn enhancements under prolonged northward interplanetary magnetic field (IMF) quiet time preconditions. They are in contrast to one another in a few aspects. Event 1 occurs in the middle of continuously increasing Pdyn wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 69 publications
1
38
0
Order By: Relevance
“…This may partially explain why the EMIC wave activity consists of longer bursts during the inbound interval. The range of solar wind dynamic pressures and background magnetic field perturbations observed during both the outbound and inbound passes through the regions of EMIC wave activity is similar to those reported in other studies of EMIC waves associated with magnetospheric compressions (e.g., Cho et al, 2016; McCollough et al, 2010; Usanova et al, 2008).…”
Section: Emic Wave Locations Spatial Extent and Amplitudessupporting
confidence: 86%
“…This may partially explain why the EMIC wave activity consists of longer bursts during the inbound interval. The range of solar wind dynamic pressures and background magnetic field perturbations observed during both the outbound and inbound passes through the regions of EMIC wave activity is similar to those reported in other studies of EMIC waves associated with magnetospheric compressions (e.g., Cho et al, 2016; McCollough et al, 2010; Usanova et al, 2008).…”
Section: Emic Wave Locations Spatial Extent and Amplitudessupporting
confidence: 86%
“…It should be emphasized that the analysis performed in section 4 was applied to the times 20 s before and after EMIC wave onsets as well as the non‐EMIC wave times, but not to the entire period of each EMIC wave event. The anisotropy can evolve during EMIC wave periods in accordance with changes in EMIC wave activity: Examples can be found in the previous work in Cho et al (). In particular, the proton anisotropy can decrease during EMIC wave duration as noted by Saikin et al ().…”
Section: Discussionmentioning
confidence: 62%
“…As has been found in many other studies, the six example Van Allen Probes passes presented in ssection 3 showed that the conditions for EMIC wave occurrence required sufficiently high densities of ring current ions [e.g., Cho et al ., ]. In many but not all the examples these waves were also associated with increased densities of either or both warm (plasma sheet) ions and thermal (cold) ions.…”
Section: Discussionmentioning
confidence: 95%